Youth Migration and Its Relation to Identity Crisis, Cultural Interaction, and Social Integration: Analytical Study (The International Journal of Educational Sciences and Arts, 2025)
The phenomenon of migration is a human occurrence that has accompanied the lives of human societies and individuals since ancient times. This phenomenon has captivated the attention of those concerned and specialists in various human disciplines, drawing their interest due to the challenges, data, and issues it presents, which span security, social, political, and economic aspects, both internationally and locally, for those countries described as sending or exporting waves of migration. It is evident that migration is a complex social phenomenon with multiple dimensions that cannot be understood or comprehended from a single scientific approach. Rather, it necessitates the use of multiple and interrelated scientific frameworks as effective methodological mechanisms for analyzing and scrutinizing this social issue from social, psychological, demographic, economic, and political perspectives, in order to encompass its various dimensions, whether internal or external migration, regular or irregular. It represents a challenge and a threat to many countries, whether they are sending or receiving host nations, due to the population, health, service, security, and economic pressures it entails. All these challenges are imposed by the migration process towards host countries, which is why we attempted to study this topic. As immediate and long-term implications for migrants and diaspora countries, the first aspect relates to the identity crisis and the extent to which it is felt or recognized as both a personal and societal challenge, manifesting as psychological feelings. Its motivations are social and represent a phase that migrants go through while living in foreign lands and experiencing alienation. The other dimension explores the nature of the relationship between migration and the processes of cultural exchange and transmission occurring for migrants, whether directly or indirectly, as they face new communities that differ entirely in their value systems, ethics, and behavioral patterns. The study aimed to clarify the nature of the social integration processes accompanying migration, the challenges they represent, how these are addressed by those countries through their legislations and laws, and the means and mechanisms imposed by the integration processes of migrants in host countries, as these are crucial processes that ensure acceptance and stability for migrants.ز             rst aspect relates
Keywords: Migration; Cultural Exchange; Identity Crisis; Integration; Alienation